Composite hydrogel based on hyaluronic acid as well as preparation method and application of composite hydrogel
By using a hyaluronic acid-based composite hydrogel, combined with EGCG, ferric ion chelates, and thermosensitive materials, the problem of insufficient ROS removal and antibacterial ability of existing hydrogels in the treatment of radiation dermatitis has been solved, achieving highly efficient ROS removal and antibacterial effects and promoting wound healing.
Patent Information
- Application Number
- CN202511187322.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2026-01-23
AI Technical Summary
Existing hydrogels are ineffective at removing radiation-induced reactive oxygen species (ROS) when treating radiation dermatitis, and lack antibacterial properties and the ability to regulate the immune microenvironment of wounds, thus affecting wound healing.
A photothermal antibacterial hydrogel was constructed by using a hyaluronic acid-based composite hydrogel, which incorporates the antioxidant natural polyphenol epigallocatechin gallic acid (EGCG) and ferric ion chelates, combined with the thermosensitive material N-vinylcaprolactam. EGCG was loaded onto the microgel to improve stability and enhance mechanical strength.
It achieves efficient removal of ROS, significantly inhibits bacteria, promotes wound healing, reduces inflammation, and achieves efficient sterilization under near-infrared light triggering, avoiding damage to normal tissue.
Smart Images

Figure CN121371280A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of hydrogel, and particularly relates to a composite hydrogel based on hyaluronic acid and a preparation method and application thereof. BACKGROUND
[0002] Radiotherapy is one of the effective means for treating cancer, and its medical demand is increasing. Statistics show that about 70% of cancer patients receive radiotherapy during the course of the disease; it contributes to 40% of cancer curative treatment. However, during the treatment process, radiation dermatitis (RISI) will occur, which is a common side effect of radiotherapy, and it plagues many cancer patients and affects the normal progress of radiotherapy. Irradiation-induced direct damage and active oxygen (ROS) amplification can cause irreversible damage to DNA, membrane lipids and proteins, leading to various cell apoptosis and necrosis. Moreover, the excessive accumulation of ROS in the wound not only triggers a severe inflammatory response by rapidly stimulating signal transduction of inflammatory cytokines, but also affects the recruitment and function of immune cells. For radiation-induced skin damage, small molecule drugs that chemically scavenge intracellular ROS have been developed, such as amifostine, ascorbic acid, resveratrol, etc. For example, hyaluronic acid microneedles loaded with amifostine achieve long-term protection of the hematopoietic system from ionizing radiation damage through sustained drug release. Light-cured hydrogel loaded with resveratrol and prussian blue nanoparticles can significantly inhibit intracellular ROS and promote the migration of fibroblasts, which helps to close the RISI wound and reconstruct the skin tissue. Some scholars have also designed a viscous hydrogel patch loaded with curcumin and tannic acid assembled nanoparticles for the care of radiation dermatitis.
[0003] Currently, natural plant compounds as active antioxidants and anti-inflammatory agents have become promising drug alternatives and are increasingly attracting widespread attention due to their enhanced biological activity, efficacy and biological safety. However, their potential use is hindered by chemical instability, low bioavailability and rapid metabolism. Although various research efforts have been made to improve the utilization of polyphenolic compounds, these methods may compromise the natural activity of the molecules and increase the risk of immunogenicity. Therefore, it is necessary to design an effective drug loading method to maintain the activity of the drug during delivery.
[0004] Compared with normal wounds, radiation-induced skin damage, including pigmentation abnormalities, ulcers, and erythema, is more complex and stubborn. Worse still, during postoperative radiotherapy, the wound condition may worsen due to potential infection of the surgical wound. Therefore, antibacterial function is indispensable in the current design of hydrogel dressings. However, current reports mainly focus on the removal of radiation-induced ROS, while ignoring the antibacterial effect of the gel.
[0005] In addition, the influence of the immune microenvironment changes at the injury site on the repair process needs to be considered. An ideal hydrogel should be able to effectively regulate the inflammatory condition of the wound, promote the proliferation of wound cells, and accelerate wound healing. SUMMARY
[0006] This section is intended to summarize some aspects of the embodiments of the present application and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of the specification of the present application in order to avoid obscuring the purpose of this section, the abstract and the title, and such simplifications or omissions cannot be used to limit the scope of the present application.
[0007] The present application discloses a synthesis method of a composite hydrogel based on hyaluronic acid, which solves the technical problems as follows:
[0008] First, in order to cope with the ROS expanded at the radiation injury site and regulate the inflammatory environment at the wound site, a natural polyphenol epigallocatechin gallate (EGCG) with outstanding antioxidant capacity is introduced into the system, and a composite hydrogel based on hyaluronic acid is synthesized.
[0009] Secondly, although the traditional hydrogel can effectively fit the wound and prevent bacterial invasion, it does not have effective antibacterial ability. We introduce natural polyphenol epigallocatechin gallate (EGCG) and trivalent iron ions here, and the chelate of the two has effective photothermal capacity. By adjusting the ratio, the hydrogel designed by the present application can effectively photothermally antibacterial but does not damage normal skin tissue.
[0010] Secondly, in view of the poor stability of natural polyphenols, a temperature-sensitive material N-vinyl caprolactam is introduced, and an acrylic acid functionalized microgel is synthesized based on it. The microgel is used to load EGCG innovatively, which not only effectively improves the stability of EGCG, but also enhances the removal of ROS when the body temperature is close to the human body temperature.
[0011] Finally, the present application constructs a composite hydrogel by physical crosslinking, and uses microgels as crosslinking points to enhance the mechanical strength of the hydrogel, and at the same time, without introducing chemical crosslinking agents, the biocompatibility is better.
[0012] In view of the above and / or problems existing in the prior art, the present application is proposed.
[0013] Therefore, the purpose of the present application is to overcome the deficiencies in the prior art, and to provide a preparation method of a composite hydrogel dressing based on hyaluronic acid for radiation skin damage.
[0014] To solve the above technical problems, the present application provides the following technical solutions, including,
[0015] Synthesis of polyNVCL-co-AAc microgel: NVCL, AAc and NaHCO3 are dissolved in water, stirring under N2 atmosphere for 1h, then BAC is added and mixed uniformly under N2 atmosphere, finally the initiator is added, the obtained mixed solution A is heated for polymerization reaction, the reaction product is cooled, filtered, centrifuged and purified to obtain polyNVCL-co-AAc microgel, which is denoted as MG;
[0016] Preparation of EGCG dimer: DA is added into a pre-cooled MSA and THF mixture to obtain solution B; EGCG is dissolved in THF and MSA to obtain solution C; solution B is added dropwise into solution C, stirred overnight in dark, concentrated under reduced pressure, extracted and vacuum dried to remove unreacted EGCG to obtain EGCG dimer;
[0017] Synthesis of EGCG-loaded microgel: MG is dissolved in MES buffer, then NHS and EDC are added in sequence, after activation, EGCG dimer aqueous solution is added, and stirring is carried out in dark to obtain EGCG-loaded microgel, which is denoted as MGE;
[0018] Preparation of composite hydrogel: MGE is dissolved in hyaluronic acid aqueous solution, then FeCl3 aqueous solution is added under stirring until the final concentration of iron ions is 0.1-50 mmol / L, and the mixture is uniformly mixed to obtain composite hydrogel;
[0019] The mass ratio of MGE to HA is 5:12.
[0020] As a preferred scheme of the preparation method of the composite hydrogel based on hyaluronic acid, in the mixed solution A, the concentration of NVCL is 1-10 mmol / L, the concentration of AAc is 0-5 mmol / L, the concentration of NaHCO3 is 0-1 g / L, and the concentration of initiator is 0-0.2 mmol / L, and the molar ratio of NVCL to BAC is 40.6:1.
[0021] As a preferred scheme of the preparation method of the composite hydrogel based on hyaluronic acid, the initiator includes APS and V50.
[0022] As a preferred scheme of the preparation method of the composite hydrogel based on hyaluronic acid, in the polymerization reaction, the reaction is carried out under N2 atmosphere, the reaction temperature is 70°C, and the reaction time is 4h.
[0023] As a preferred scheme of the preparation method of the hyaluronic acid-based composite hydrogel, in the solution B, the concentration of DA is 1-10 mmol / L, and the volume ratio of MSA to THF is 1:5; in the solution C, the concentration of EGCG is 1-15 mmol / L, and the volume ratio of MSA to THF is 2235:1; and the volume ratio of the solution B to the solution C is 6:19.
[0024] As a preferred scheme of the preparation method of the hyaluronic acid-based composite hydrogel, the extraction is that the product is dissolved in H2O, and unreacted EGCG is removed by extraction with ethyl acetate through a separation funnel, and the unreacted EGCG moves to the organic layer, and the ethylamine-bridged EGCG dimer remains in the water layer; and the extraction is performed 5-7 times.
[0025] As a preferred scheme of the preparation method of the hyaluronic acid-based composite hydrogel, in the synthesis process of the EGCG microgel, the mass / volume ratio of MG, NHS, EDC, EGCG and MES buffer is 140:345:240:3.5:275.
[0026] Still another object of the present application is to provide a hyaluronic acid-based composite hydrogel.
[0027] Still another object of the present application is to provide an application of the hyaluronic acid-based composite hydrogel in preparing a dressing for radioactive skin damage.
[0028] The present application has the following advantages:
[0029] (1) The natural polyphenol epigallocatechin gallate (EGCG) with excellent antioxidant performance is selected in the present application, which can effectively scavenge the excess ROS induced by radiation and improve the inflammation of the wound.
[0030] (2) The microgel of the present application realizes the loading of EGCG through chemical bonding, which not only effectively improves the stability of EGCG, but also the microgel itself has temperature responsiveness, and the hydrogel matrix can further accelerate the release through temperature change (network expansion after photothermal heating), forming a "nanoparticle-hydrogel" dual-stage controlled release system.
[0031] (3) Through the photothermal synergistic effect (near-infrared light triggering), the local temperature of the present application can be raised to above 50℃ within 10 minutes, realizing a bacterial killing rate of >99.9% (such as Staphylococcus aureus and Escherichia coli), which is significantly better than traditional antibiotics. The present application has the characteristics of high photothermal conversion efficiency and accurate temperature control, and avoids the damage to normal tissues caused by excessive heating.
[0032] (4) The present application constructs a composite hydrogel by physical cross-linking, and uses microgels as cross-linking points to enhance the mechanical strength of the hydrogel, without introducing chemical cross-linking agents, and has better biocompatibility.
[0033] (5) The dressing prepared from the hyaluronic acid-based hydrogel can effectively promote the healing of radiation-induced skin ulcers, improve post-radiotherapy skin damage, promote angiogenesis, and reduce inflammation. BRIEF DESCRIPTION OF DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings needed in the embodiment description will be briefly introduced as follows. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor. Among them:
[0035] Figure 1 Synthesis process of EGCG-loaded microgels.
[0036] Figure 2 Preparation process of hyaluronic acid-based composite hydrogel.
[0037] Figure 3 Temperature response kinetics test of microgels.
[0038] Figure 4 ROS generated by X-ray in water.
[0039] Figure 5 Adhesion strength test of composite hydrogel.
[0040] Figure 6 Photo-thermal response of composite hydrogel.
[0041] Figure 7 Intracellular free radical scavenging of composite hydrogel.
[0042] Figure 8 Example of therapeutic effect of composite hydrogel on radiation-induced skin damage in mice. DETAILED DESCRIPTION
[0043] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application will be described in detail below.
[0044] In the following description, many specific details are set forth in order to provide a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without departing from the scope of the present application, therefore the present application is not limited to the specific embodiments disclosed below.
[0045] Second, the term "one embodiment" or "an embodiment" as may appear in various places of the specification is not necessarily referring to the same embodiment, nor is it necessarily a separate or alternative embodiment.
[0046] The raw materials used in the present application are all commercially available.
[0047] The substances and their abbreviations are as follows:
[0048] N-vinylcaprolactam (NVCL), acrylic acid (AAc), N,N'-bis(acryloyl)cystamine (BAC), poly-NVCL-co-AAc microgels (MG), methanesulfonic acid (MSA), tetrahydrofuran (THF), aminoacetaldehyde diethyl acetal (DA), epigallocatechin gallate (EGCG), 2-morpholinoethanesulfonic acid (MES), N-hydroxysuccinimide (NHS), 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), EGCG-loaded microgels (MGE), hyaluronic acid (HA), tannic acid (TA), gallic acid (GA), azobis-isobutyramidine hydrochloride (V50), ammonium persulfate (APS).
[0049] The materials prepared in the embodiments of the present application are tested for performance as follows:
[0050] 1) The MGE solution is highly diluted. The particle size of the microgels is measured by dynamic light scattering (DLS) at a temperature range of 25-55°C with an interval of 2.5°C, and after being stabilized for 2 min at the specified temperature.
[0051] 2) Scavenging of X-ray generated free radicals in water by MGE
[0052] DCFH-DA probe is used for detection.
[0053] DCFH-DA (10 mM, 12.5 μL) is dissolved in dimethyl sulfoxide (DMSO, 0.5 mL), 2 mL of 0.01 M NaOH solution is added, and the mixture is reacted in the dark for 30 min. Then, the reaction is terminated by adding pH = 7.2 phosphate buffer (10 mL) to obtain a DCFH solution. The prepared DCFH solution is stored in the dark under ice bath conditions for subsequent use.
[0054] Next, the sample is prepared for testing:
[0055] (i) water group (3 mL of water);
[0056] (ii) MGE group (2.9 mL MGE (aqueous solution) (1 mg / mL) + 0.1 mL water);
[0057] (iii) DCFH group (0.1 mL DCFH solution + 2.9 mL water);
[0058] (iv) DCFH + X-ray group (0.1 mL DCFH solution + 2.9 mL MGE (aqueous solution) (1 mg / mL) + X-ray);
[0059] (v) DCFH + MGE + X-ray group (0.1 mL DCFH solution + 2.9 mL MGE (aqueous solution) (1 mg / mL) + X-ray).
[0060] After irradiation with X-ray (160 KV, 25 mA) for 2 min, all samples were centrifuged and the corresponding supernatant was obtained, and the emission spectrum of the sample was tested using a transient steady-state fluorescence spectrometer, with a test range of 500-600 nm and a step length of 2 nm.
[0061] 3) Adhesion strength test
[0062] Shear adhesion experiments were performed on the hydrogels. Fresh pigskin was cleaned with hot water and the grease was scraped off. After freeze-drying, it was cut into a size of 2.5 x 3 cm, and then soaked in 1 x PBS solution for a certain period of time to make it completely wet. After wiping off the excess water on the surface, it was tested. Then it was adhered to a PE plastic sheet (2.5 x 7.5 cm) using a commercial cyanoacrylate adhesive. Two pieces of the substrate adhered to the PE plate were taken, and the hydrogel (2.5 x 2 x 0.1 cm) was placed between the substrates, and then manually pressed to eliminate air bubbles to make the surface of the hydrogel completely contact with the substrate. The shear adhesion experiment was performed on a tensile machine with a test speed of 5 mm / min. The adhesion strength was calculated by dividing the maximum load by the initial contact area. The adhesion of the hydrogel to the pigskin was tested as above. All the above experiments were repeated at least three times. The measurement data was expressed as mean ± standard deviation (x ± s).
[0063] 4) Photo-thermal response of composite hydrogels
[0064] The HA / Fe 3+ / MGE 25 Hydrogels were made into circular sheets with a diameter of 10 mm and a thickness of 10 mm, and then irradiated with an 808 nm laser at different power densities (0.25, 0.5, 0.75, 1 W / cm -2 ) for 10 min. The temperature rise of the gel was recorded using an infrared camera.
[0065] 5) Intracellular ROS scavenging
[0066] L929 cells were seeded in 96-well plates at a density of 3 x 10 4Cells were seeded at 1 x 105 / well in 24-well plates containing each group of samples and incubated at 37°C for 24 h. The extraction solution was added for 12 h, and the ROS in the cells was observed by fluorescence microscopy after staining with DCFH-DA probe and 16 Gy X-ray irradiation for 24 h.
[0067] 6) In vivo radioprotection evaluation
[0068] Establishment of radiation-induced skin damage model: After the right hind limb was depilated, the mice were anesthetized, and then the right hind limb skin was exposed to 40 Gy X-rays at a dose rate of 2 Gy / min. All irradiated mice were randomly divided into Control, HA / Fe 3+ Hydrogel, HA / Fe 3+ / MGE 25 Hydrogel 3 groups. After different treatments, the mice were fixed with 3M adhesive tape. The injured area of the skin of the hind limb of the mice was observed and photographed at the set time point.
[0069] Example 1
[0070] This example provides a preparation method of a composite hydrogel, which is described with reference to Figure 1 、 Figure 2 , and specifically as follows:
[0071] 1) Preparation of microgels
[0072] Synthesis of polyNVCL-co-AAc microgels (MG): 7.3 mmol of NVCL, 0.37 mmol of AAc and 33.3 mg of NaHCO3 were dissolved in 45 mL of deionized water, and the solution was flushed with nitrogen for 1 h. Then, 0.18 mmol of BAC was added, and the mixing and stirring were continued for 1 h under N2 atmosphere (the molar ratio of NVCL to BAC was 40.6:1). Finally, 0.05 mmol of APS (dissolved in 5 mL of deionized water) was added to initiate the polymerization reaction, and the solution was stirred and heated to 70°C under N2 atmosphere. After 4 h, the heating was stopped, the reaction mixture was cooled to room temperature, filtered through Whatman #1 filter paper, and purified by high-speed centrifugation (10000 rpm, 30 min, x3) for standby use.
[0073] 2) Preparation of EGCG dimer: In a flask, 1.2 mL of pre-cooled methanesulfonic acid (MSA) and tetrahydrofuran (THF) mixed solution (v / v = 1:5) was added, and 145 μL of ethylenediamine (DA, 1 mmol) was slowly added dropwise under magnetic stirring, marked as solution B. Another 50 mL three-necked flask was prepared, and 2.29 g of epigallocatechin gallate (EGCG, 5 mmol) was dissolved in a mixed solvent of 3.8 mL of THF and 1.7 μL of MSA. Solution B was slowly added dropwise to the EGCG solution, and after the addition was completed, the reaction was stirred at room temperature for 12 h in the dark. After the reaction was completed, the solvent was removed by rotary evaporation (40°C) under reduced pressure, and then placed in a vacuum drying box (25°C) overnight. The obtained crude product was dissolved in 10 mL of ultrapure water and transferred to a separatory funnel, and extracted with 10 mL of ethyl acetate. The aqueous phase was collected to obtain an aqueous solution of ethylenediamine bridged EGCG dimer. The obtained product was stored at -20°C for subsequent experiments.
[0074] 3) Synthesis of EGCG-loaded microgel (MGE): 140 mg of MG was dissolved in 3.5 mL of MES buffer, and 345 mg of NHS and 240 mg of EDC were added in turn. After activation for 2 h, 1 mL of epigallocatechin gallate (EGCG) dimer solution (275 mg / mL) was added, and the mixture was stirred in the dark for 10 h. The obtained product was centrifuged and purified to obtain EGCG-loaded microgel, marked as MGE.
[0075] 4) Preparation of composite hydrogel: 25 mg of MGE was dissolved in 1 mL of 6% w / v hyaluronic acid (HA) aqueous solution, and then FeCl3 aqueous solution was added under stirring until the final concentration of iron ions was 30 mM. The mixture was continuously stirred at room temperature for 10 min to obtain the composite hydrogel.
[0076] Figure 3 For the temperature response kinetics test of MGE microgel, it can be seen that the particle size of the microgel decreases with the increase of temperature, and the volume phase transition temperature is about 35.2°C, indicating that the microgel has obvious temperature responsiveness.
[0077] Figure 4 For the scavenging of X-ray generated free radicals (ROS) in water by microgel, it can be seen that 1 mg / mL of MGE has an effective scavenging ability for the free radicals generated by 3 Gy X-ray in water, with a scavenging rate of more than 80%. It shows that the prepared microgel effectively retains the activity of EGCG and has effective free radical scavenging ability.
[0078] Figure 5 For the adhesion strength test of the composite hydrogel, it can be seen that with the addition of MGE, the adhesion of the composite hydrogel to pigskin gradually increases.
[0079] Figure 6For the photo-thermal response of the composite hydrogel, it can be seen that the composite hydrogel has excellent photo-thermal performance, and can be raised to above 50℃ within 10 min under the irradiation of 808 nm laser with a power density of 1 W / cm 2 The composite hydrogel can effectively photo-thermal antibacterial under the irradiation of 808 nm laser with a power density of 1 W / cm
[0080] Figure 7 For the intracellular free radical scavenging of the composite hydrogel, it can be seen that the composite hydrogel can effectively scavenge X-ray induced intracellular ROS.
[0081] Figure 8 For the treatment effect of the composite hydrogel on the radiation-induced skin damage of the mouse leg, the mouse leg was irradiated with 40 Gy X-ray, and the irradiated area was treated with different gels after 10 days. The treatment effect was observed after 14 days of treatment. The results show that the damage degree of the leg in the gel group without adding MGE is improved compared with the control group, because the hydrogel can provide a moist healing environment, the porous structure allows oxygen exchange, and hyaluronic acid has certain anti-inflammatory effect. After adding MGE, the damage degree is the smallest and the treatment effect is the best after treatment, because the loaded EGCG has excellent ROS scavenging ability and anti-inflammatory properties.
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 1 is that the epigallocatechin gallate (EGCG) dimer solution is adjusted to a tannic acid (TA) dimer aqueous solution, and the rest of the preparation process is the same as that of Example 1, and a microgel loaded with TA is prepared.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 1 is that the epigallocatechin gallate (EGCG) dimer solution is adjusted to a tannic acid (TA) dimer aqueous solution, and the rest of the preparation process is the same as that of Example 1, and a microgel loaded with TA is prepared.
[0086] The microgels prepared in the above examples and comparative examples were tested for performance, and the comparison results with Example 1 are shown in Table 1.
[0087] Table 1
[0088]
[0089] As can be seen from the above table, the microgel loaded with EGCG has the best free radical scavenging ability.
[0090] Example 2
[0091] The difference between this embodiment and embodiment 1 is that the final concentration of MGE is adjusted to 50 mg / mL, i.e. 50 mg MGE is dissolved in 1 mL of HA (6% w / v) aqueous solution, and the rest of the preparation process is the same as that of embodiment 1 to prepare the composite hydrogel.
[0092] Example 3
[0093] The difference between this embodiment and embodiment 1 is that the final concentration of MGE is adjusted to 15 mg / mL, i.e. 15 mg MGE is dissolved in 1 mL of HA (6% w / v) aqueous solution, and the rest of the preparation process is the same as that of embodiment 1 to prepare the composite hydrogel.
[0094] Example 4
[0095] The difference between this embodiment and embodiment 1 is that the final concentration of MGE is adjusted to 5 mg / mL, i.e. 5 mg MGE is dissolved in 1 mL of HA (6% w / v) aqueous solution, and the rest of the preparation process is the same as that of embodiment 1 to prepare the composite hydrogel.
[0096] Comparative Example 3
[0097] The difference between this comparative example and embodiment 1 is that the final concentration of MGE is adjusted to 0 mg / mL, i.e. 1 mL of HA (6% w / v) aqueous solution does not contain MGE, and the rest of the preparation process is the same as that of embodiment 1 to prepare the composite hydrogel.
[0098] The composite hydrogels prepared in the above examples and comparative examples are tested for performance, and the comparison results with embodiment 1 are shown in Table 2.
[0099] Table 2
[0100]
[0101]
[0102] As can be seen from the above table, adjusting the concentration of MGE has a significant effect on the mechanical properties of the composite hydrogel, which is due to the non-covalent interaction of MGE with hyaluronic acid and ferric ions, MGE as a crosslinking point effectively enhances the crosslinking density, thereby improving the gel strength. At the same time, the addition of MGE can enhance the adhesion strength of the gel to the substrate, because MGE contains a large number of hydrophilic catechol functional groups, which are similar in structure to mussel adhesion proteins, and can produce non-covalent interactions with a variety of substrates, such as proteins on the skin. On the other hand, the introduction of MGE also improves the toughness of the hydrogel. The synergistic effect of the two makes the hydrogel exhibit better adhesion properties to various substrates. According to the results in the above table, the MGE concentration in the present application is 25 mg / mL, which can obtain the best technical effect.
[0103] Comparative Example 4
[0104] The difference between the present example and Example 1 is that the molar ratio of NVCL to BAC is adjusted to 15:1, and the rest of the preparation process is the same as that of Example 1, to obtain microgels MG.
[0105] Comparative Example 5
[0106] The difference between the present example and Example 1 is that the molar ratio of NVCL to BAC is adjusted to 30:1, and the rest of the preparation process is the same as that of Example 1, to obtain microgels MG.
[0107] Comparative Example 6
[0108] The difference between the present example and Example 1 is that the molar ratio of NVCL to BAC is adjusted to 66.7:1, and the rest of the preparation process is the same as that of Example 1, to obtain microgels MG.
[0109] Comparative Example 7
[0110] The difference between the present example and Example 1 is that the amount of AAc added is adjusted to 0, and the rest of the preparation process is the same as that of Example 1, to obtain microgels MG.
[0111] Comparative Example 8
[0112] The difference between the present example and Example 1 is that the amount of NaHCO3 added is adjusted to 0, and the rest of the preparation process is the same as that of Example 1, to obtain microgels MG.
[0113] The microgels MG prepared in the above comparative examples are observed, and the comparison results with Example 1 are shown in Table 3.
[0114] Table 3
[0115]
[0116]
[0117] As can be seen from the above table, the molar ratio of NVCL to BAC is optimal when it is 40.6:1, and acrylic acid needs to be added to balance the charge and improve the stability of the microgels, and appropriate NaHCO3 needs to be added to adjust the pH of the system.
[0118] In summary, the present application realizes the loading of EGCG by chemical bonding, which not only effectively improves the stability of EGCG, but also the microgels themselves have temperature responsiveness, and the hydrogel matrix can further accelerate the release through temperature changes (network expansion after photothermal heating), forming a "nanoparticle-hydrogel" dual-stage controlled release system.
[0119] It should be noted that the above examples are only used to illustrate the technical solutions of the present application but not limit the present application. Although the present application is described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or equivalently replaced, without departing from the spirit and scope of the technical solutions of the present application, which should be covered in the scope of the claims of the present application.
Claims
1. A method for preparing a hyaluronic acid-based composite hydrogel, characterized by: Comprising, Synthesis of polyNVCL-co-AAc microgel: NVCL, AAc and NaHCO3 are dissolved in water, then BAC is added and mixed uniformly, and then initiator is added, and the obtained mixed solution A is heated for polymerization reaction, and the reaction product is cooled, filtered, and centrifuged for purification to obtain polyNVCL-co-AAc microgel, which is denoted as MG; Preparation of EGCG dimer: DA is added to a pre-cooled MSA and THF mixture to obtain solution B; EGCG is dissolved in THF and MSA to obtain solution C; solution B is added dropwise to solution C, and stirred overnight in the dark, concentrated under reduced pressure, and vacuum dried, and then extracted to remove unreacted EGCG to obtain EGCG dimer; Synthesis of EGCG-loaded microgel: MG is dissolved in MES buffer, and then NHS and EDC are sequentially added, and after activation, EGCG dimer aqueous solution is added, and stirred in the dark to obtain EGCG-loaded microgel, which is denoted as MGE; Preparation of composite hydrogel: MGE is dissolved in hyaluronic acid aqueous solution, and then FeCl3 aqueous solution is added under stirring until the final concentration of iron ions is 0.1-50 mmol / L, and the mixture is uniformly mixed to obtain composite hydrogel; The mass ratio of MGE to HA is 5:
12.
2. The method for preparing a hyaluronic acid-based complex hydrogel according to claim 1, characterized by: In the mixed solution A, the concentration of NVCL is 1-10 mmol / L, the concentration of AAc is 0-5 mmol / L, the concentration of NaHCO3 is 0-1 g / L, and the concentration of initiator is 0-0.2 mmol / L, and the molar ratio of NVCL to BAC is 40.6:
1.
3. The method for preparing a hyaluronic acid-based complex hydrogel according to claim 2, characterized by: The initiator includes APS and V50.
4. The method for preparing a hyaluronic acid-based complex hydrogel according to claim 1, characterized by: In the polymerization reaction, the reaction is carried out under N2 atmosphere, the reaction temperature is 70°C, and the reaction time is 4 h.
5. The method for preparing a hyaluronic acid-based complex hydrogel according to claim 1, characterized by: In the solution B, the concentration of DA is 1-10 mmol / L, and the volume ratio of MSA to THF is 1:
5.
6. The method for preparing a hyaluronic acid-based complex hydrogel according to claim 1, characterized by: In the solution C, the concentration of EGCG is 1-15 mmol / L, and the volume ratio of MSA to THF is 2235:1; the volume ratio of solution B to solution C is 6:
19.
7. The method for preparing a hyaluronic acid-based complex hydrogel according to claim 1, wherein: The extraction is performed by dissolving the product in H2O, and then unreacted EGCG is removed by extraction with ethyl acetate through a separation funnel, and unreacted EGCG moves to the organic layer, while EGCG dimer bridged by ethylamine remains in the water layer; the extraction is performed 5-7 times.
8. The method for preparing a hyaluronic acid-based complex hydrogel according to claim 1, characterized by: In the synthesis of EGCG-loaded microgel, the mass / volume ratio of MG, NHS, EDC, EGCG, and MES buffer is 100-150:320-350:200-250:3.5:
275.
9. A hyaluronic acid-based composite hydrogel prepared by the preparation method of any one of claims 1-8.
10. Use of the hyaluronic acid-based composite hydrogel of claim 9 in the preparation of a dressing for radioactive skin damage.